Biomechanical study of the thyroid cartilage: A model of bi-digital strangulation. (September 2019) - Gagnon, C.; Boismery, S.; Godio-Raboutet, Y.; Tuchtan, L.; Bartoli, C.; Adalian, P.; Chaumoitre, K.; Piercecchi-Marti, M.-D.; Thollon, L.
Highlights: The thyroid cartilage shows a sexual dimorphism. There is a different behavior according to sex and morphology during strangulation. The fracture pattern is similar between sexes. Abstract: The presence of fracture on neck elements is an indication of violence. Both the hyoid bone and the larynx can be damaged by a strangulation mechanism. Thyroid cartilage, more specifically, may present lesions in response to this mechanical stress. These lesions result in fractures at the bases of the horns of the thyroid cartilage. This study focuses on the thyroid cartilage behavior in cases of bi-digital strangulation, using an anthropometric and biomechanical approach. To develop a biomechanical model, we performed an anthropometric study taking into account 14 distances measurements as well as 3 measurements of angles. These measures allowed us to determine a significant sexual dimorphism between individuals. Then, we define 6 morphologies models, composed of 3 females and 3 males individuals. In order to visualize the ossification of the cartilage, each model has been tested with bone properties. Strangulation cases were simulated by applying an imposed velocity of 0.4 m/s then 1 m/s. We observed different behaviors of the thyroid cartilage according to the sex and the morphology.